Geração de prole virtual por reprodução simulada aplicada ao problema de pessoas desaparecidas - Esguerra, Martha Isabel Cárdenas (2011)
Virtual reality has applications in different fields of knowledge such as Engineering, Science, Arts, Entertainment and Education. In this work, virtual reality is used to help solving the problem of missing persons. The proposed methodology uses simulated diploid reproduction of virtual characters carefully modeled taking into account the traits of the missing person’s parents. The parents models are generated in the age of son at the moment of disappearance and genetic characteristics of both parents are stored into their genomic data structure, which will be used to construct pools of male and female gametes to be used in a simulated fecundation. The descendants are generated with the same age of the missing person at the time of disappearance. Through an interactive process, a plausible model of the missing person is selected among the generated descendants and its genomic data structure is saved. The parents’ models and corresponding data structures are updated to reflect the age of the missing person at search time. Next, the genomic data structure of the missing person is updated with the information contained in the updated data structure of the parents, and an updated model of the missing person is generated. This updated model is a plausible model, upon which perturbations can be applied to generate several plausible variants. Case studies are presented that demonstrate the potentials of the proposed methodology.